Going home: Social work across and about borders. (March 2016) - Wehbi, Samantha; Parada, Henry; George, Purnima; Lessa, Iara
This article explores the idea of returning home to the South to practise social work. Through our experiences as members of diasporic communities living in the North, we examine how we are implicated in the tensions that surround social work practice and research as efforts to internationalize continue to grow. Specifically, we explore the following themes: the neo-managerial underpinnings of the internationalization of social work; neocolonialism embedded in occupying the role of the reluctant expert; and what we carry with us to help us negotiate the tensions that we experience in navigating our practices across borders.